2022
DOI: 10.3390/ijms23094728
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Investigation of G6PDH Gene in Strawberry: Evolution and Expression Analysis during Development and Stress

Abstract: As one of the key enzymes in the pentose phosphate pathway (PPP), glucose-6-phosphate dehydrogenase (G6PDH) provides NADPH and plays an important role in plant development and stress responses. However, little information was available about the G6PDH genes in strawberry (Fragaria × ananassa). The recent release of the whole-genome sequence of strawberry allowed us to perform a genome-wide investigation into the organization and expression profiling of strawberry G6PDH genes. In the present study, 19 strawberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In winter wheat, TaG6PDH (Triticum aestivum G6PDH) expression was upregulated under cold stress and exogenous ABA application, suggesting that TaG6PDH positively responds to cold stress and ABA [129]. Similarly, FaG6PDH positively regulated cold tolerance in strawberry [130], and in silico bioinformatics analysis of 19 FaG6PDH promoters revealed the presence of at least one stress-responsive cis-acting element [131]. An early stress response would involve the OPPP, which represents a true metabolic sensor during the response to various stresses.…”
Section: Drought and Heatmentioning
confidence: 99%
“…In winter wheat, TaG6PDH (Triticum aestivum G6PDH) expression was upregulated under cold stress and exogenous ABA application, suggesting that TaG6PDH positively responds to cold stress and ABA [129]. Similarly, FaG6PDH positively regulated cold tolerance in strawberry [130], and in silico bioinformatics analysis of 19 FaG6PDH promoters revealed the presence of at least one stress-responsive cis-acting element [131]. An early stress response would involve the OPPP, which represents a true metabolic sensor during the response to various stresses.…”
Section: Drought and Heatmentioning
confidence: 99%
“…Under abiotic stress, it has been reported that the organic carbon of plant species results in a shift from EMP to PPP, in a percentage even higher than 50% [33,34]. PPP enhances NADPH production [35,36], promoting the cells' metabolic activity, including the carbonand nitrogen-metabolizing enzymes (Figure 1b). The shift to the PPP was also conducive to nitrate reduction and the formation of RuBP, which promoted the regenerative capacity of RuBP in the Calvin-Benson cycle.…”
Section: Glucose Metabolism (Emp and Ppp) And Growth In Bn And Ov Pla...mentioning
confidence: 99%
“…The number of G6PDH genes changes significantly among plant species. Thus, 19 G6PDH genes in strawberry (Fragaria × ananassa) [18], 9 in soybean (Glycine max) [35], 6 in Arabidopsis thaliana [8], 5 in rice (Oryza sativa), Arabidopsis tauchii, tomato (Solanum lycopersicum) [27], and maize (Zea mays) [27], and 4 G6PDH genes in rubber tree (Hevea brasiliensis) [36] and einkorn wheat (Triticum urartu) [37] have been reported. Therefore, the four CaG6PDH genes identified in this work indicate that pepper is among the species with the lowest number of G6PDH genes.…”
Section: The Pepper Genome Contains Four Cag6pdh Genes Which Are All ...mentioning
confidence: 99%
“…Maize plants enclose five genes and, among them, the ZmG6PDH4 gene length is almost 18 kb with 9 exons and two large introns [27]. Strawberries have 19 G6PDH genes with 10 to 15 exons, but the largest gene which corresponds to FaG6PD14 has less than 7 kb [18]. All these examples with many introns/exons with different lengths indicate the great diversity of the G6PDH gene structures in higher plants.…”
Section: The Pepper Genome Contains Four Cag6pdh Genes Which Are All ...mentioning
confidence: 99%
See 1 more Smart Citation